EFFECT OF INTELLECTUAL CAPABILITIES (IQ) AND LEARNING MOTIVATION AT THE RESULTS OF ACCOUNTING SUBJECT ON SMA LABSCHOOL RAWAMANGUN - A Andartari; Santi Susanti; Vidia Andriani (Faculty of Economics, State University of Jakarta., 2013)
This study aims to determine how much influence the intellectual ability (IQ) and learning motivation on student learning outcomes in subjects at high school Accounting Labschool Rawamangun. Which is located on Jl. Pemuda, Rawamangun UNJ complex, and was conducted in May and June 2011. The study was the correlation method, the entire student population was at high school Labschool Rawamangun, with a population of affordable class XI IPS with the number of 158 students, by taking a sample of 110 responden.Instrument which is used in the form of kuesi oner, in the form of 35 statements for Learning and Motivation free variable data Intellectual ability (IQ) and Learning Outcomes in Accounting students can directly from the school. In variable Motivation of 35 statement filed there are 5 statement is declared invalid or drop (r count> r table). The results of the calculation of the variable motivation to learn has a reliability of 0.961. These results further stated reliably used to obtain data. From the research results can be described the effect of intellectual ability and motivation to learn the Accounting Learning Outcomes show a positive relationship is a positive influence between intellectual ability of students and Motivation Against Student Results At Subjects Accounting.Keywords: the intellectual ability (IQ), Motivation and Learning Outcomes Accounting